AN EARTH SCIENTIST'S PERIODIC TABLE OF THE ELEMENTS AND THEIR IONS - Railsback L.B. (My University, 2003)
A new Earth Scientist's Periodic Table of the Elements and Their Ions presents the naturally occurring charged species commonly encountered by geoscientists, as well as elemental forms, and it is organized by charge. The new table therefore shows many elements multiple times, unlike the conventional table. As a result, trends, patterns, and interrelationships in mineralogy, soil and sediment geochemistry, igneous petrology, aqueous geochemistry, isotope geochemistry, and nutrient chemistry become apparent in this new table. The new table thus provides a more effective framework for understanding geochemistry than the conventional, and purely elemental, periodic table. [PERIODICAL ABSTRACT]
Keywords: EARTH; SCIENCE; IONS; CHEMICAL ELEMENTS